Effects of human-induced habitat changes on site-use patterns in large Amazonian Forest mammals. (March 2023) - Quintero, Simón; Abrahams, Mark I.; Beirne, Christopher; Blake, John; Carvalho, Elildo; Costa, Hugo C.M.; de Paula, Milton José; Endo, Whaldener; Haugaasen, Torbjørn; Lima, Marcela Guimarães Moreira; Michalski, Fernanda; Mosquera, Diego; et al.
Abstract: The Amazon is one of the most diverse biomes around the globe, currently threatened by economic and industrial development and climate change. Large mammals are keystone species, playing an important role in ecosystem structure and function as ecological engineers, while being highly susceptible to deforestation, habitat degradation, and human exploitation. Using a unifying hierarchical Bayesian spatial approach, we examine the site-use patterns of four large Amazonian Forest mammals and their relationships to anthropogenic factors at a biome-wide scale. Our results showed that species' patterns of site use are correlated with human induced habitat changes, and that this correlation is species-specific. The white-lipped peccary shows highest site-use estimates within strict protected areas, affected by proximity to urban areas and benefiting from indigenous territories, the tapir responding slightly to proximity to burned forested areas, while the giant armadillo and the jaguar were primarily affected by vegetation cover loss; disturbances related to the colonization of the Amazon. Our findings contribute to the understanding of how human-induced environmental changes influence the site-use patterns of these four large mammals, and inform future conservation and land use planning. Transboundary conservation efforts, empowering and integrating native (indigenous and non-indigenous) communities in land governance schemes, involving the private sector and securing the commitment of developed countries are important paths for the protection and sustainability of the globally-crucial Amazon rainforest.